Effects of IT Maturity and Freedom of Choice regarding relations between the Service Provider and its clients - Bernt Krohn Solvang (International Journal of Business Science & Applied Management (IJBSAM), 2006)
The roles of the public servants seem to change towards increased service attitudes influenced by degree of IT Maturity and towards increased degree of problem solving influenced by increased degree of freedom in action. The quality of communication seems to be mainly influenced by the degree of equity between the partners. However, for amateur users increased IT maturity could increase the quality of the communication between the servant and the client. By increased focus on roles and customer needs managers are able to lay a foundation for increased relationship quality and by that increase customer loyalty. Based on three Norwegian case studies the paper is explorative in nature.
Keywords: 650; IT maturity; freedom of choice; relations; roles; communication; needs